Serials and Satisfaction - O’Sullivan, Sean (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2013)
The idea of “satisfaction” privileges narratives that seek to fulfill a promise of wholeness or containment. Such an idea runs counter to the gapped, partial, and suspended work of serial narrative. This essay considers the perils of satisfaction as a goal or byproduct of seriality, examining how serials in practice—from Middlemarch and Great Expectations to Lost and Mad Men—theorize and complicate our sense of resolved conclusion, and how they articulate the ungovernable excess of energy and possibility that serials, at their most narratively engaged, inevitably generate.